Use of genetically manipulated Salmonella typhimurium strains to evaluate the role of human sulfotransferases in the bioactivation of nitro‐ and aminotoluenes. (29th February 2016) - Glatt, Hansruedi; Sabbioni, Gabriele; Monien, Bernhard H.; Meinl, Walter
Abstract : Various nitro‐ and aminotoluenes demonstrated carcinogenic activity in rodent studies, but were inactive or weakly active in conventional in vitro mutagenicity assays. Standard in vitro tests do not take into account activation by certain classes of enzymes. This is true in particular for sulfotransferases (SULTs). These enzymes may convert aromatic hydroxylamines and benzylic alcohols, two major classes of phase‐I metabolites of nitro‐ and aminotoluenes, to reactive esters. Here it is shown that expression of certain human SULTs in Salmonella typhimurium TA1538 or TA100 strongly enhanced the mutagenicity of various nitrotoluenes and nitro‐ and amino‐substituted benzyl alcohols. Human SULT1A1, SULT1A2, and SULT1C2 showed the strongest activation. The observation that some nitrotoluenes as well as some aminobenzyl alcohols were activated by SULTs in the absence of cytochromes P450 implies that mutagenic sulfuric esters were formed at both the exocyclic nitrogen and the benzylic carbon, respectively. Nitroreductase deficiency (using strain YG7131 instead of TA1538 for SULT1A1 expression) did not affect the SULT‐dependent mutagenicity of 1‐hydroxymethylpyrene (containing no nitro group), moderately enhanced that of 2‐amino‐4‐nitrobenzyl alcohol, and drastically attenuated the effects of nitrobenzyl alcohols without other substituents. The last finding suggests that either activation occurred at the hydroxylamino group formed by nitroreductase or the nitro group (having a strong –M effect) had to be reduced to an electron‐donating substituent to enhance the reactivity of the benzylic sulfuric esters. The results pointed to an important role of SULTs in the genotoxicity of nitrotoluenes and alkylated anilines. Activation occurs at nitrogen functions as well as benzylic positions. Environ. Mol. Mutagen. 57:299–311, 2016. © 2016 Wiley Periodicals, Inc.